Fooled by Glowing? The Role of Social Commerce Constructs in Building Trust on Intention To Buy - Pramesti, Betrice Gita; Iqbal Daulay, Muhammad Yasser (JURNAL MANAJEMEN MOTIVASI, 2025)
This study examines the effect of social commerce constructs on purchase intention through trust in overclaimed skincare products among Bengkulu City consumers. Using a quantitative approach with 220 respondents via purposive sampling, data were analyzed using Structural Equation Modeling. Results show that social commerce constructs significantly influence trust, which in turn positively affects purchase intention. However, social commerce constructs do not directly influence purchase intention. These findings suggest that building consumer trust is essential for skincare businesses to optimize marketing strategies on social media